2021
DOI: 10.1111/aor.14055
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of two individualized antithrombotic protocols in HeartWare HVAD recipients

Abstract: We previously reported low rates of pump thrombosis and hemorrhagic stroke, but increased bleeding, under our original antithrombosis protocol (P1) in HeartWare recipients. We designed and implemented a revised protocol (P2) to reduce complexity and bleeding. Thrombelastography and PFA-100 guide antiplatelet titration.Goals for P2 were altered to decrease antiplatelet use and anticoagulation intensity. We compared the incidence and rates of gastrointestinal bleeding (GIB), embolic (eCVA) and hemorrhagic (hCVA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…At the same time, studies such as the MOMENTUM 3 Trial based on the use of HeartMate 3 (Abbott, Chicago, USA) showed a reduction of strokes also in females 26,27 . Moreover, novel tendencies are represented by a low‐intensity anti‐coagulation strategy for LVAD patients 27,28 . However, as also highlighted by our findings and by the existence of sex difference in stroke occurrence in the general population, it is still not clear if females and males should undergo the same postoperative anti‐coagulation therapies or if these therapies should acknowledge possible sex differences 28 .…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…At the same time, studies such as the MOMENTUM 3 Trial based on the use of HeartMate 3 (Abbott, Chicago, USA) showed a reduction of strokes also in females 26,27 . Moreover, novel tendencies are represented by a low‐intensity anti‐coagulation strategy for LVAD patients 27,28 . However, as also highlighted by our findings and by the existence of sex difference in stroke occurrence in the general population, it is still not clear if females and males should undergo the same postoperative anti‐coagulation therapies or if these therapies should acknowledge possible sex differences 28 .…”
Section: Discussionmentioning
confidence: 66%
“…26,27 Moreover, novel tendencies are represented by a low-intensity anti-coagulation strategy for LVAD patients. 27,28 However, as also highlighted by our findings and by the existence of sex difference in stroke occurrence in the general population, it is still not clear if females and males should undergo the same postoperative anti-coagulation therapies or if these therapies should acknowledge possible sex differences. 28 Thus, it is strongly recommended to include a significant percentage of women in the upcoming LVAD clinical studies to further investigate the need for sex-oriented anti-coagulation strategies.…”
Section: Discussionmentioning
confidence: 76%
“…For comparison, some CT NRRs reported in the contemporary 6,16–29 and original literature 30–53 are shown in Figure 3. In most instances, these NRRs differ from each other and also from the manufacturer ranges, especially for C/ADP.…”
Section: Resultsmentioning
confidence: 99%
“…The Siemens product information CT NRRs are shown by the green horizontal dashed lines. Figure A shows NRRs from some contemporary literature as obtained from the recent literature search (see Methods), and reflecting information from the past 3 years 6,16–29 . Figure B shows NRRs from some early literature as otherwise reviewed in Reference 10 30–53 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation